High performance nano-zirconium silicate adsorbent for efficient removal of copper (II), cadmium (II) and lead (II). Issue 2 (June 2015) - Mahmoud, Mohamed E.; Nabil, Gehan M.; Mahmoud, Sarah M.E.
Graphical abstract: Highlights: Nano-zirconium silicate (ZrSiO4 -NPs) was explored as a novel adsorbent. The metal selectivity properties of ZrSiO4 -NPs were evaluated. High capacity values (4.500–1.400 mmol g −1 ) were characterized. The experimental controlling factors were studied and evaluated. The surface reaction between Cu(II) and ZrSiO4 -NPs was confirmed. Abstract: In this research paper, zirconium silicate material, in the form of nanoparticles (ZrSiO4 -NPs), was explored as a high performance, novel and efficient adsorbent for extraction and removal of some divalent metal ions. The metal selectivity properties of ZrSiO4 -NPs were studied and evaluated from the distribution coefficients of a series of divalent metal ions. The incorporated selectivity characters were found to follow the order: Cu(II) > Cd(II) > Pb(II) > Ni(II) > Co > Mg (II) > Ca(II). The metal binding and uptake capacity values of Cu(II), Cd(II) and Pb(II) as the highest extracted metal ions by ZrSiO4 -NPs were investigated as a function of pH, contact time, adsorbent dosage and initial metal ion concentration using the batch equilibrium technique. The adsorption capacity values of Cu(II), Cd(II) and Pb(II) were characterized as 4.500, 2.100 and 1.400 mmol g −1, respectively using 5.0 mg of the adsorbent at pH 7.0. The adsorption processes were studied, evaluated and found to follow the postulates of Langmuir and BET isotherm models. The surface reaction between metal ions such as Cu(II) and ZrSiO4 -NPs was confirmed using FT-IR, SEM and TGA.